2015
DOI: 10.1007/s10803-015-2610-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-Presentation and the Role of Perspective Taking and Social Motivation in Autism Spectrum Disorder

Abstract: We compared self-presentation abilities of 132 children and adolescents with autism spectrum disorders (ASD) to those of 41 typically developing (TD) peers, and examined the potential link with their social motivation and perspective taking. Participants introduced themselves to an interviewer in a baseline condition (without incentive) and a self-promotion condition (with incentive). Children with ASD (6-12 years) were just as likely as or even more likely than TD children to highlight personal characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…This task was designed to have lower verbal demands than previous tasks testing self-presentation in autism (e.g. Barbaro and Dissanayake 2007; Begeer et al 2008; Scheeren et al 2010, 2015). Children were asked to test three computer games run through MATLAB.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This task was designed to have lower verbal demands than previous tasks testing self-presentation in autism (e.g. Barbaro and Dissanayake 2007; Begeer et al 2008; Scheeren et al 2010, 2015). Children were asked to test three computer games run through MATLAB.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has shown, however, that reputation management is possible in some adolescents and adults on the autism spectrum (Cage et al 2013, 2016; Scheeren et al 2015), which raises questions about the underlying abilities that might explain variability in explicit and implicit reputation management in autistic individuals. Two main hypotheses have been proposed to explain why autistic individuals have difficulties with reputation management.…”
Section: Individual Differences In Reputation Managementmentioning
confidence: 99%
See 3 more Smart Citations